Analisis Kemampuan Literasi Matematika Siswa Dalam Memecahkan Masalah Model Pisa Pada Materi Aritmatika Sosial di MTs Negeri Kalimantan Timur - Abdul Razak; Ahmad Maulana Syafii; Nanda, Firnanda Pradana Putra (Absis: Mathematics Education Journal, 2023)
The purpose of the study was to characterize the mathematical literacy of eighth-grade State MTs in East Kalimantan students as they solved PISA model questions with social arithmetic content. Because the research describes the actual conditions of the research subjects, it falls under the category of qualitative research. One high category student, one medium category student, and one low category student from MTs Negeri East Kalimantan's class VIII made up the research subjects. An initial ability test, a PISA model test on social math topics, and interviews with study respondents were used as the research data gathering techniques. The study's findings demonstrate that pupils with strong category abilities are able to decipher issues and use social math concepts to solve issues in everyday life. Due to calculation errors, students with medium category abilities can solve issues effectively but with poor accuracy. Because they are less likely to have strong reading abilities, students in the low ability category cannot draw suitable conclusions from the presented questions.